The Effect of False Advertising on Consumer Online Purchase Behavior with the Mediating Effect of e-WOM: Consumers in Malaysia - Ahmed, Ahmed Michail Awad; Othman, Abdul Kadir Bin (Information Management and Business Review, 2024)
Advertising is one of the main contributors to the rising number of online shoppers worldwide. The use of advertising in this digital era has become a powerful tool for the persuasion of consumers. However, some organizations have adopted false advertising as their marketing strategy. The purpose of this study is to analyze the factors that influence consumers’ online shopping behavior. The study focuses on the three independent constituent factors of false advertising, namely, unethical advertising, misleading information, and deception. The dependent variable is online purchase behavior. A questionnaire was distributed to 588 individuals who shopped once or more from the top e-commerce platforms in Malaysia. The questionnaire underwent validation and reliability assessments, followed by the collection and analysis of responses using SPSS software. The findings indicate that False advertising can have significant effects on consumer online purchase behavior in Malaysia. Through the use of misleading or false information, companies can manipulate consumer perceptions and ultimately influence their buying decisions. This can lead to several negative consequences for consumers, including financial losses, disappointment with purchased products, and erosion of trust in online shopping.